2023
DOI: 10.1039/d2dt03360g
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) complexes of cyclams with N-(2,2,2-trifluoroethyl)-aminoalkyl pendant arms as potential probes for 19F magnetic resonance imaging

Abstract: A series of Cu(II) complexes with cyclam-based ligands containing two N-(2,2,2-trifluoroethyl)-aminoalkyl pendant arms in 1,8-positions (L1: 1,2-ethylene spacer, L2: 1,3-propylene spacer; L3: 1,4-butylene spacer) was studied in respect to potential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 90 publications
1
12
1
Order By: Relevance
“…33 Observed T 1 for the Cu(II)-H 2 L complexes (ca. 5-9 ms) is slightly lower than values found for isomeric Cu(II) complexes of 1,8-(tfe-NHCH 2 CH 2 ) 2 cyclam (7-12 ms) 42 theory. 30 Preliminary calculation confirmed that the contribution of relaxation is set of complexes negligible and, thus, only the dipolar relaxation mechanism was considered.…”
Section: F Nmr Relaxation Of the Complexescontrasting
confidence: 53%
See 2 more Smart Citations
“…33 Observed T 1 for the Cu(II)-H 2 L complexes (ca. 5-9 ms) is slightly lower than values found for isomeric Cu(II) complexes of 1,8-(tfe-NHCH 2 CH 2 ) 2 cyclam (7-12 ms) 42 theory. 30 Preliminary calculation confirmed that the contribution of relaxation is set of complexes negligible and, thus, only the dipolar relaxation mechanism was considered.…”
Section: F Nmr Relaxation Of the Complexescontrasting
confidence: 53%
“…5–9 ms) is slightly lower than values found for isomeric Cu( ii ) complexes of 1,8-(tfe-NHCH 2 CH 2 ) 2 cyclam (7–12 ms) 42 whereas the average M⋯F distances found in the Cu( ii )–H 2 L complexes are somewhat longer (6.36 Å) than those observed for the Cu( ii )–1,8-(tfe-NHCH 2 CH 2 ) 2 cyclam (5.6–6.1 Å). 42 However, the signals of the Cu( ii )–H 2 L complexes are very broad. The / T 1 ratio is ca.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…1) containing six fluorine atoms and a study of its transition metal complexes was reported. 47 The results showed that such a concept is viable and brought promising data especially for the Co 2+ complex. 47 Fig.…”
Section: Introductionmentioning
confidence: 96%
“…47 The results showed that such a concept is viable and brought promising data especially for the Co 2+ complex. 47 Fig. 1 Ligands mentioned in the text.…”
Section: Introductionmentioning
confidence: 96%